Conducting In-Depth Interviews via Mobile Phone with Persons with Common Mental Disorders and Multimorbidity: The Challenges and Advantages as Experienced by Participants and Researchers - Azadé Azad (MDPI AG, 2021)
Qualitative interviews are generally conducted in person. As the coronavirus pandemic (COVID-19) prevents in-person interviews, methodological studies which investigate the use of the telephone for persons with different illness experiences are needed. The aim was to explore experiences of the use of telephone during semi-structured research interviews, from the perspective of participants and researchers. Data were collected from mobile phone interviews with 32 individuals who had common mental disorders or multimorbidity which were analyzed thematically, as well as field notes reflecting researchers’ experiences. The findings reveal several advantages of conducting interviews using mobile phones: flexibility, balanced anonymity and power relations, as well as a positive effect on self-disclosure and emotional display (leading to less emotional work and social responsibility). Challenges included the loss of human encounter, intense listening, and worries about technology, as well as sounds or disturbances in the environment. However, the positive aspects of not seeing each other were regarded as more important. In addition, we present some strategies before, during, and after conducting telephone interviews. Telephone interviews can be a valuable first option for data collection, allowing more individuals to be given a fair opportunity to share their experiences.